The Social Dimension of the Orthodox Liturgy: From Biblical Dynamism to a Doxological Liturgism - Basileiadēs, Petros Bas. (Review of ecumenical studies, 2017)
A historical and theological journey in 12 steps, from the early Biblical origin to later Patristic and contemporary expression of the Orthodox liturgy, in order to uncover the social dimension of Christian liturgy. Some of the causes are analyzed in brief: the marginalization of the Antiochene tradition, an overdose eschatology, the modern understanding of the Bible, the gradual loss of the prophetic character of the Church, which is more evident in the Bible, and the marginalization - until the Holy and Great Council of the Orthodox Church - of its witnessing responsibility, have resulted in a significant legacy that hinders any real Biblical and liturgical renewal. The experiment of the Church of Greece that launched nearly 20 years ago an official, albeit unsuccessful, liturgical renewal project. The final proposal is a combination of both this neglected prophetic character and the prevailing eschatological dimension of the Orthodox faith, with all that these imply for an authentic and genuine Orthodox liturgical practice.